Thought, Attitude and Action: The Struggle of an International PhD Student-Mother during the COVID-19 Pandemic in Australia - Fridani, Lara; Elfiah, Ulfa; Handayani, Selfi; Ali, Aschawir (Journal of International Students, 2020)
The purpose of this narrative study was to explore how an international PhD student-mother, who has a young child, negotiated and coped with the challenges to complete her studies during the COVID-19 pandemic. Multiple semi-structured interviews were adopted to collect narrative data. Anchored in a thematic analysis, qualitative data showed that the participant encountered such challenges as the skills of managing academic time and activities, difficulty in focusing on studying, worries about family conditions in Indonesia and financial needs. We concluded that physical, mental and spiritual strengths of an individual derived from family and community support play a pivotal role in thinking of, managing, and coping with various challenges during the COVID-19 pandemic.